Dairy Enterprise—600 Lactating Cows (Freestall) - Dhuyvetter, Kevin C.; Harner III, Joseph P.; Brouk, Micheal (My University, 2014)
This publication describes the production costs and returns for a dairy enterprise with 600 lactating cows in a freestall system.
MF2441_2014_04
Keywords: MF2441; Economics; Livestock; MF